Cooperation-aided solutions for data delivery in challenged wireless networks - Yang, Shengbo (2013)
To satisfy people’s increasing demand for network connectivity and Internet access, several new wireless network paradigms, such as Mobile Ad Hoc Networks (MANETs), Vehicular Ad Hoc Networks (VANETs) and Pocket Switched Networks (PSNs), are emerging in recent years. These networks not only extend the wireless network coverage and make several new applications possible, but also bring great challenges.